The Relationship Between Math Anxiety and Cognitive Flexibility on Students’ Mathematical Critical Thinking Ability - Arianto, Halil; Wayan Rumite (International Journal of Technology and Education Research, 2026)
Mathematical critical thinking is an essential skill that supports students in solving complex problems and making logical decisions in learning mathematics. However, students’ ability to think critically is often influenced by both emotional and cognitive factors. This study aims to examine the relationship between math anxiety and cognitive flexibility on students’ mathematical critical thinking ability. This research employed a quantitative approach with a correlational design involving junior high school students selected through purposive sampling. Data were collected using a math anxiety questionnaire, a cognitive flexibility scale, and a mathematical critical thinking test. The data were analyzed using descriptive statistics, Pearson correlation, and multiple regression analysis. The results show that students’ math anxiety is at a moderate level (M = 68.45; SD = 8.72), cognitive flexibility is at a moderate–high level (M = 74.12; SD = 7.95), and mathematical critical thinking ability is at a moderate level (M = 70.36; SD = 9.10). Furthermore, math anxiety has a significant negative correlation with mathematical critical thinking ability (r = -0.52, p < 0.05), while cognitive flexibility has a significant positive correlation (r = 0.61, p < 0.05). The results of multiple regression analysis indicate that math anxiety (β = -0.41, p < 0.05) and cognitive flexibility (β = 0.48, p < 0.05) simultaneously influence students’ mathematical critical thinking ability. These findings suggest that students with lower levels of anxiety and higher cognitive flexibility tend to demonstrate better critical thinking skills in mathematics. Therefore, improving students’ mathematical critical thinking requires both reducing math anxiety and enhancing cognitive flexibility through appropriate instructional strategies.